A critical review of available composite damage growth test data under fatigue loading and implications for aircraft sustainment. (15th January 2020) - Molent, L.; Haddad, A.
Abstract: With growing interest in moving towards a slow-growth design or in-service sustainment basis for aircraft composite and bonded structures, there is a need to establish whether the growth of typical damage in such structure under fatigue loading is systematic and therefore predicable. To this end this paper presents test data from the available literature and draws some general conclusions from this review. The results, which were mainly from aerospace grade carbon/epoxy material systems support the hypothesis that damage growth in composites is a function of applied fatigue cycles and evolves systematically. Also, simple damage metrics retrievable from field level non-destructive inspection are able to capture some, and possibly in some cases, the majority, of the physical nature of the evolution. The work herein sets the foundation for the development of deployable bridged-scale assessments of the effect of damage on the residual static strength and durability performance of composite aircraft structure to support airworthiness decision making.